Metabolism and Pharmacokinetics of San-Huang-Xie-Xin-Tang, a Polyphenol-Rich Chinese Medicine Formula, in Rats and Ex-Vivo Antioxidant Activity. (7th June 2011) - Shia, Chi-Sheng; Hou, Yu-Chi; Juang, Shin-Hun; Tsai, Shang-Yuan; Hsieh, Pei-Hsun; Ho, Lu-Ching; Chao, Pei-Dawn Lee
Abstract : San-Huang-Xie-Xin-Tang (SHXXT), a widely used Chinese herbal formula, consists of rhizomes of Rheum officinale, roots of Scutellaria baicalensis and rhizomes of Coptis chinesis . This study investigated the metabolism and pharmacokinetics of polyphenols in SHXXT, including baicalin, baicalein, wogonin, emodin, aloe-emodin, rhein and chrysophanol. The quantitation methods of SHXXT decoction and rat serum using high performance liquid chromatography were developed and validated in this study. After oral administration of SHXXT decoction to rats, the parent forms of various constituents and their conjugated metabolites in serum were determined before and after hydrolysis with β -glucuronidase and sulfatase. The results showed that only free form of rhein can be quantitated, whereas the parent forms of coptisine, palmatine, berberine, baicalein, wogonin, emodin, aloe-emodin and chrysophanol were not detected in serum. The glucuronides of baicalein, wogonin, emodin, aloe-emodin, rhein and chrysophanol were the predominant forms in bloodstream. In order to evaluate the in vivo antioxidant activity of SHXXT, the serum metabolite of SHXXT was prepared, characterized and followed by evaluation of the effect on AAPH-induced hemolysis. The results indicated that metabolites of SHXXT exhibited significant free radical scavenging activity. We suggest that biologists redirect their focus to the bioactivity of the conjugated metabolites of these polyphenols.